ETHANOL FERMENTATION POTENCY OF WILD YEAST ON BAMBOO RHYZOSPHERE - Anton Muhibuddin (Journal of Environmental Engineering and Sustainable Technology, 2016)
Bamboo plant rhizosphere known as source of simbiotic useful microorganisms, including yeast. Wild yeast explored should be tested it’s adaptability to new ecology especially nutritional source availability. The research aim to get potential yeast which can work well during fermentation process in apple juice substrate.We were isolated yeast from three different locations: Ketawanggede District, Karangploso District, and Lowokwaru District. All locations was located around Malang city.Result showed that there were found 13 isolates yeast: Protomyces sp, Agaricostilbum sp1, Agaricostilbum sp2, Agaricostilbum sp3, Debaryomyces sp1, Debaryomyces sp2, Debaryomyces sp3,  Trigonopsis sp1, Trigonopsis sp2, Udeniomyces sp1, Udeniomyces sp2, Ascoidea hylocieti, and Komagataella sp. Diversity index indicates medium category to low category and dominance index in all location indicates high category.Fermentation test showed improvements in observation variables at 24 and 72 hours including temperature, cells number, and alcohol percentage. The highest alcohol percentage were 11.6% and 10% that produced by the treatment of Agaricostilbum sp3 and Trigonopsis sp1 respectively.Keyword: Yeast, bamboo plant rhizosphere, apple juice, and fermentation.